Trubkový držák lyžiny rally vozu Škoda Fabia Super 2000 - Ondruch, Marek (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2013)
Tato diplomová práce se zabývá konstrukčním návrhem trubkového držáku ližiny na rally vůz Škoda Fabia Super 2000. Ke zhodnocení stávající varianty a navazujících navrhovaných konstrukčních variant je využito MKP programu. Na základě zjištěných výsledků byla vybrána nejvhodnější varianta, která zároveň splňuje požadovanou tuhost a snížení hmotnosti.

This diploma thesis “Tubular Skid Holder of Skoda Fabia Super 2000 Rally Car” is aimed to engineering design of tubular skid holder of rally car Skoda Fabia Super 2000. There is used FEM software for analysis s evaluation of current variant and following variants of engineering design. The most relevant final variant design, which is consistent with asked stiffness and reduction of weight, was chosen based on findings.
Tubular Skid Holder of Skoda Fabia Super 2000 Rally Car
Keywords: Ližina; Škoda Fabia Super 2000; ochranné prvky; rallye; tuhost; trubkový držák; Sump guard; Škoda Fabia Super 2000; protective elements; rally; stiffness; tubular holder